Vertical and seasonal distribution of Anopheles (Kerteszia) in Ilha Comprida, Southeastern Brazil - Ueno, Helene Mariko; Forattini, Oswaldo Paulo; Kakitani, Ina (Revista de Saúde Pública, 2007)
OBJECTIVE: Anopheles bellator e An. cruzii are vectors of the so-called bromeliad-malaria, typical of conserved areas. The objective was to evaluate the seasonal and vertical distribution of these anophelines, aiming at assessing the risk of malaria transmission. METHODS: In the municipality of Ilha Comprida, Southeastern Brazil, CDC light traps baited with dry ice were placed fortnightly from 17:00 to 20:00, at one, six and 12 meters high from September 2001 to September 2002. Association between An. bellator and An. cruzii densities and weather were assessed by Spearman coefficient and comparisons among heights and species densities were made by Mann-Whitney non-parametric test. RESULTS: A total of 55,226 mosquitoes were caught: 1,341 were An. bellator (2.4% of Culicidae), 278 at one meter, 261 at six meter and 802 at 12m high. Following the same sequence, An. cruzii was represented by 452, 1,032 and 4,420 adults, totalizing 5,904 mosquitoes (10.7%). There was a positive correlation between densities of both species and daily maximum temperature, and between density of An. bellator and thermal amplitude. The densities were higher for both species at tree canopy. At the three levels, the density of An. cruzii was higher. CONCLUSIONS: The acrodendrophilic behavior of these species was confirmed, remarkably in An. cruzii. After aggressive measures of control, these anophelines have remained in this region, but they are not under entomological surveillance. The persistent transmission of malaria and increasing tourism activities in this region highlight the need for surveillance of these species.